The The Mediating Role Of Trust In The Influence Of Viral Marketing And Online Consumer Reviews On Purchasing Decisions Skintific Product In TikTok - Dewi Murni; Muhartini Salim (UNIVED Press, 2024)
Online shopping in Indonesia will continue to increase along with technological advances, Data collected by APJII and Suara.com shows that